Formation of tissue factor-bearing leukocytes during and after cardiopulmonary bypass - Shibamiya, Aya; Tabuchi, Noriyuki; Chung, Jihwa; Sunamori, Makoto; Koyama, Takatoshi (Thrombosis and Haemostasis, 2004)
During cardiopulmonary bypass (CPB), the extrinsic coagulation system initiated by tissue factor (TF) is a major procoagulant stimulus. TF is present in surgical wounds and could be expressed on activated monocytes. However, recent studies have suggested that collagen stimulation rapidly induces TF by leukocyte-platelet complex formation. Therefore, the appearance of TF-bearing leukocytes and their effect on promoting coagulation were investigated in 5 patients undergoing coronary bypass surgery. Neutrophils and monocytes positive for CD41a and TF increased abruptly in circulating blood during CPB. Their increase was most prominent in blood pooled in the pericardial cavity. Monocytes, but not neutrophils positive for TF showed a second peak one day after operation, which accords with the increase in TF mRNA levels in leukocytes. Similarly, an increase in leukocytes positive for TF accords with the activated factor X generation assay using isolated leukocytes, and with an increase in thrombin-antithrombin complex in circulating blood. The second increase in TF-positive monocytes seems to be responsible for these coagulation parameters that remained high one day after operation. After 10 min of blood incubation stimulated by collagen in vitro, simulating activation in the pericardial cavity, significant increases in neutrophils and monocytes positive for TF and platelet were observed. Our present study suggested the involvement of two distinct mechanisms for the appearance of TF-bearing leukocytes responsible for promoting coagulation: the quick appearance being partly explained by the formation of leukocyte-platelet complex that occurs mainly in the pericardial cavity, and the slow appearance via transcriptional activation in monocytes.
Keywords: Tissue factor (TF); cardiopulmonary bypass (CPB); leukocytes; platelet